System hardening and security monitoring for IoT devices to mitigate IoT security vulnerabilities and threats - Choi, Seul Ki; Yang, Chung Huang; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2018)
The advent of the Internet of Things (IoT) technology, which brings many benefits to our lives, has resulted in numerous IoT devices in many parts of our living environment. However, to adapt to the rapid changes in the IoT market, numerous IoT devices were widely deployed without implementing security by design at the time of development. As a result, malicious attackers have targeted IoT devices, and IoT devices lacking security features have been compromised by attackers, resulting in many security incidents. In particular, an attacker can take control of an IoT device, such as Mirai Botnet, that has insufficient security features. The IoT device can be used to paralyze numerous websites by performing a DDoS attack against a DNS service provider. Therefore, this study proposes a scheme to minimize security vulnerabilities and threats in IoT devices to improve the security of the IoT service environment.
Keywords: Internet of thing (IOT); IoT security; Living environment; Security by designs; Security incident; Security monitoring; Security threats; Security vulnerabilities; IoT security; Security monitoring; Security threat; System hardening